2009
DOI: 10.4251/wjgo.v1.i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Telomere function in colorectal cancer

Abstract: Colorectal cancer is the third most common form of cancer and the second leading cause of cancer-related death in the western world. Tumour cells acquire the hallmarks of cancer during the carcinogenic selection process. Cell immortality is one of the principal features acquired during this process which involves the stabilization of telomere length. It is achieved mainly, by telomerase activation. Thus, the discovery of telomeres and telomerase allowed an understanding of the mechanisms by which cells can bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…However, several studies, including ours, did not find a significant relationship between telomere length and telomerase levels and/or activity (Frías and Morán 2009; Rampazzo et al , 2010). Several studies suggested that hTERT might increase the malignant potential of tumours beyond just preservation of telomere length.…”
Section: Discussioncontrasting
confidence: 59%
“…However, several studies, including ours, did not find a significant relationship between telomere length and telomerase levels and/or activity (Frías and Morán 2009; Rampazzo et al , 2010). Several studies suggested that hTERT might increase the malignant potential of tumours beyond just preservation of telomere length.…”
Section: Discussioncontrasting
confidence: 59%
“…A multivariate analysis by Sanz-Casla et al examined the impact of telomerase activity in prognosis in 103 CRC patients undergoing surgery, which showed that by adjusting for tumor stage, telomerase activity could be utilized to predict the risk of death or recurrence of CRC [154]. Thus, quantification of telomerase activity may be a useful method of evaluating prognosis in patients with CRC [155]. …”
Section: The Gi Tract Cancers Telomeres and Telomere Maintenance Mementioning
confidence: 99%
“…Wang et al (7) observed that the expression of E-cadherin, β-catenin, glycogen synthase kinase-3β (GSK-3β), cyclin D1 and c-myc was positive in LSTs. Human telomerase reverse transcriptase (hTERT/Hest2/TP2), the main subunit involved in telomerase reverse transcription, is considered as one of the most important proteins affecting telomerase activity (8,9). However, hTERT expression in LSTs has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%